Non-O1Vibrio cholerae bacteremia in an infant, first case report from Pakistan - Sarwar, Samreen; Hannan, Abdul; Sultana, Qamar; Saleem, Sidrah; Sohail, Muhammad; Arshad, Muhammad Usman; Rasool, Karam (The Journal of Infection in Developing Countries, 2016)
To the best of our knowledge, Non-O1 Vibrio cholerae (NOVC) bacteremia has never been documented in Pakistan. This case report is the first reported case of bacteremia in an infant due to NOVC in Pakistan. A neonate was admitted to a hospital with fever and no history of diarrhea. The isolate was identified biochemically and serologically and was sensitive to all the drugs tested as per CLSI 2014 guidelines.